Malocclusion: Prevalence and Determinants among Adolescents of Karachi, Pakistan - Tariq, Rabia; Khan, Muhammad Tahir; Afaq, Ashar; Tariq, Sobia; Tariq, Yasir; Khan, Sana Shakil (European Journal of Dentistry, 2023)
Objectives The aim of this study was to determine the prevalence of malocclusion and its associated demographic and clinical factors in young adolescents (13–15 years) of Karachi, Pakistan.Materials and Methods An epidemiological survey included 500 young adolescents of registered schools, madrassas (Islamic education system), and shop workers of Gulshan-e-Iqbal Town. It was a cross-sectional analytical study design. Multistage random sampling technique was used to enroll participants. The pattern of occlusion was recorded with other related features using Angle's classification. Health status was recorded through World Health Organization-guided indices (decayed, missing, and filled permanent teeth [DMFT], community periodontal index of treatment needs [CPITN], and body mass index [BMI]). The information, thus, obtained was analyzed through SPSS using the chi-squared test and regression models.Results Forty four percent of the participants were female, while overall estimated prevalence of malocclusion in young adolescents of Karachi was 57.4%. After adjustments, participants going to any kind of education system had less malocclusion in comparison to those who were not going to any education system (adjusted odds ratio [aOR] = 0.305, 95% confidence interval [CI] = 0.12–0.73); mother's education especially higher level (aOR = 2.02, 95% CI = 1.08–3.75) and presence of periodontal disease (aOR = 1.57, 95% CI = 1.06–2.33) were significantly associated with malocclusion.Conclusion This study showed that the class I malocclusion is prevalent in the local community. Demographic factors like gender, age, self-reported ethnicity, and BMI did not show any significant role. Education or knowledge of parents and young adolescents does play an influential role in decreasing malocclusion. Young adolescents, who are more prone to oral health problems at an early age, would have more chances to develop occlusal discrepancies.
Keywords: malocclusion; DMFT index; CPITN index; young adolescents; prevalence